Sports Nutrition (MDPI - Multidisciplinary Digital Publishing Institute, 2023)
For this Special Issue, research leaders in sports nutrition were approached and invited to submit current reviews in their areas of expertise. The topics are novel and wide-ranging, and include updates and insights on protein, dietary patterns, and nutritional interventions to support sleep, older athletes, and sports performance; pre-exercise nutrition; supplementation with betaine, iron, and creatine; and sports nutrition research methodologies for body composition and muscle glycogen analysis. A major emphasis in all of the papers was a focus on strengths and weaknesses for various sports nutrition strategies, and insights for future research. This Special Issue on sports nutrition provided current updates in many core areas, with insights from leading experts for future research. Hopefully, scientific understanding will be advanced as these ideas are converted into novel research designs and discoveries.